Analisis Faktor Yang Mempengaruhi Minat Nasabah Dalam Menggunakan BSI Mobile Pada Bank Syariah Indonesia KC Medan Ahmad Yani - Rindi Nabila Syahputri; Ahmad Perdana Indra (STIKes Ibnu Sina Ajibarang, 2023)
The objective of this article is to examine the elements that impact the inclination of customers of Indonesian Islamic banks, specifically those in KC Medan Ahmad Yani, to utilize mobile banking. Technology has significantly influenced people's lives, and the banking industry has utilized the internet to enhance their services. This has resulted in the emergence of mobile banking, which refers to banking services accessed through mobile phones or, in other words, phone banking. Mobile banking, along with services like ATMs and credit cards, has become essential for Indonesian banks to expand their target market. Currently, mobile banking serves as a primary focal point and an effective operational strategy for banks to enhance their services.The purpose of this analysis is to identify the factors that influence customers' interest in using mobile banking and the strategies employed to increase customer engagement. Additionally, the study aims to ascertain whether mobile banking can be employed as a marketing strategy to drive customer growth at Bank Syariah Indonesia KC Medan Ahmad Yani. Data collection for this research is conducted through a questionnaire, which includes inquiries intended to gather relevant information.